Progestin-Primed Ovarian Stimulation Protocol for Patients With Endometrioma - Yang, Ai-Min; Feng, Teng-Fei; Han, Yan; Zhao, Zhi-Ming; Wang, Wei; Wang, Yi-Zhuo; Zuo, Xiao-Qi; Xu, Xiuhua; Shi, Bao-Jun; Li, Lipeng; Hao, Gui-Min; Cui, Na (Frontiers in Endocrinology, 2022)
Objective To evaluate the pregnancy outcomes of progestin-primed ovarian stimulation (PPOS) protocol for patients with endometrioma underwent in vitro fertilization/intra-cytoplasmic sperm injection embryo transfer (IVF/ICSI-ET). Design Observational retrospective cohort study. Setting University affiliated reproductive center. Study Participants 605 infertile patients with endometrioma underwent IVF/ICSI-ET from January 2016 to March 2021 were included in this study. Methods Multivariable logistic regression analyses were conducted to determine the independent effect of controlled ovarian stimulation (COS) protocols on reproductive outcomes of first embryo transfer (ET) cycles. The live birth was primary outcome, the implantation rate, biochemical pregnancy, clinical pregnancy and ongoing pregnancy were secondary outcomes. Results Compared to PPOS protocol, the probability of implantation showed no significant difference with ultra-long gonadotrophin-releasing hormone agonist (GnRHa) protocol and gonadotrophin-releasing hormone antagonist (GnRHant) protocol (OR 1.7, 95% CI 0.9-3.1, OR 1.2, 95% CI 0.7-2.1, respectively). The PPOS protocol was correlated with a significantly lower biochemical pregnancy and clinical pregnancy than ultra-long GnRHa protocol in the multivariable logistic regression analysis (OR 2.3, 95% CI 1.1-4.9, OR 2.4, 95% CI 1.1-5.3, respectively). However, there was no significant difference in terms of biochemical pregnancy, clinical pregnancy and ongoing pregnancy between PPOS and GnRHant protocol (OR 1.4, 95% CI 0.7-2.7, OR 1.3, 95% CI 0.7-2.4, OR 1.1, 95% CI 0.6-2.3, respectively). In addition, compared to PPOS protocol, ultra-long GnRHa protocol and GnRHant protocol demonstrated no statistical difference in ongoing pregnancy (OR 2.0, 95% CI 0.9-4.5, OR 2.1, 95% CI 0.6-2.3, respectively). Notably, the ultra-long GnRHa protocol was associated with a significant higher probability of live birth than PPOS protocol both in crude analysis and multivariable logistic regression analysis (OR 2.6, 95% CI 1.3-5.1, OR 2.5, 95% CI 1.1-5.7, respectively). Nevertheless, no statistical difference was found in live birth between PPOS and GnRHant protocol either in crude analysis and multivariable logistic regression analysis (OR1.2, 95% CI 0.6-2.3, OR 1.2, 95% CI 0.6-2.5, respectively). Conclusions Based on the reproductive outcomes of the first ET cycles in patients with endometrioma, PPOS protocol may associated with inferior reproductive outcomes in terms of biochemical pregnancy, clinical pregnancy and live birth than ultra-long GnRHa protocol. However, there was no significant difference in implantation rate, clinical pregnancy, ongoing pregnancy and live birth between PPOS and GnRHant protocol.